Chemical Constituents of the Leaves of Campanula takesimana (Korean Bellflower) and Their Inhibitory Effects on LPS-induced PGE2 Production - Yutong Qi; Se-In Choi; So-Ri Son; Hee-Soo Han; Hye Shin Ahn; Yu-Kyong Shin; Sun Hee Lee; Kyung-Tae Lee; Hak Cheol Kwon; Dae Sik Jang (Plants, 2020)
Campanula takesimana Nakai (Campanulaceae; Korean bellflower) is one of the endemic herbs of Korea. The plant has been used as traditional medicines for treating asthma, tonsillitis, and sore throat in Korea. A hot water extract of the leaves of C. takesimana exhibited a significant inhibitory effect on lipopolysaccharide (LPS)-stimulated prostaglandin E2 (PGE2) production. Repetitive chromatographic separation of the hot water extract led to the isolation of three new neolignan glucosides, campanulalignans A–C (1–3), with 15 known compounds (4–18). The structures of new compounds 1–3 were elucidated by analyzing nuclear magnetic resonance (NMR) spectroscopic data, along with high resolution quadrupole time of flight mass (HR-Q-TOF-MS) spectrometric data. Among the isolates, simplidin (7), 5-hydroxyconiferaldehyde (11), icariside F2 (12), benzyl-α-l-arabinopyranosyl-(1″→6′)-β-d-glucopyranoside (13), and kaempferol 3-O-β-d-apiosyl (1→2)-β-d-glucopyranoside (15) were isolated from the Campanulaceae family for the first time. The isolates (1, 2, and 4–18) were assessed for their anti-inflammatory effects on LPS-stimulated PGE2 production on RAW 264.7 cells. 7R,8S-Dihydrodehydrodiconiferyl alcohol (5), 3′,4-O-dimethylcedrusin 9-O-β-glucopyranoside (6), pinoresinol di-O-β-d-glucoside (8), ferulic acid (10), 5-hydroxyconiferaldehyde (11), and quercetin (18) showed significant inhibitory effects on LPS-stimulated PGE2 production.